Analysis of the Development Characteristics and Influencing Factors of Freezing Temperature Field in the Cross Passage - Yan Zhuang; Junhao Chen; Jian Zhang; Jianlin Wang; Han Li (Advances in Civil Engineering)
Based on the analysis of the temperature measurement data of the Shanghai Metro Line 15 cross passage freezing project, it was found that the gray silt layer of cross passage No. 2 outperforms that of cross passage No. 1 on the freezing effect, which is mainly attributed to the large loss of cooling capacity in the latter passage. Within the same stratum, the soil temperature at the duct piece is higher than that of the deep soil. When the soil freezes for 45 days, the temperatures of the sandy silt and gray silt layers of the same cross passage drop to −8.25°C and −6.91°C, respectively, indicating that the freezing effect of the sandy silt layer is better than that of the gray silt layer. Moreover, simulations were performed for deviation freezing pipes, nondeviation freezing pipes, and different freezing pipe diameters in the cross passage No. 1, respectively. It was found that the maximum difference of the closure completion time between the deviation and nondeviation freezing pipes is 6 days. Furthermore, for deviation freezing pipes and nondeviation freezing pipes at the center of the cross passage, the minimum difference in the freezing wall thickness reduces from 0.45 mm after 20 days of freezing to 0.06 mm after 45 days of freezing, indicating that the difference in the freezing wall thickness gradually weakens as freezing develops gradually. The deviation freezing pipe increases the spacing of freezing pipes in the deep soil. As the pipe spacing increases, the influence of the pipe diameter on the closure completion time of the freezing wall decreases.